On the Andean endemic genus Scotiotrichia Mosely (Trichoptera: Glossosomatidae: Protoptilinae): description of the larva and biogeographic patterns of the Andean Protoptilinae - Sganga, Julieta Valeria (2024)
Scotiotrichia Mosely is a monospecific genus of the subfamily Protoptilinae, endemic to the Andean region. Scotiotrichia ocreata is known exclusively from the adults and has been recorded from the Patagonia of Argentina and Chile. To associate the larva of this species we examined adults collected in Chubut province using Malaise and light traps, and larvae and metamorphotypes collected manually or with a Surber net sampler. The larva of Scotiotrichia ocreata is characterized by the morphology of the tarsal claws, with basal process short and thick, arising perpendicular to the base of the claw, and basal seta long and broad; the chaetotaxy of the legs, especially the number and distribution of feathered setae; the presence of three accessory teeth on the anal prolegs; and six pairs of long setae on abdominal tergum IX. Additionally, we gathered information regarding the distribution of all the known Protoptilinae species found in the Andean region sensu lato to study their distributional patterns using a track analysis. We found two generalized tracks, one austral, that corresponds to the Subantartic subregion, and another northern, at the Páramo province of the South American transition zone. These tracks represent ancestral biotas that were fragmented by geologic or climatic events.